Trichotillomania with regrowth of curly hair in the area treated with minoxidil. - Kannattukunnel, R.; Phiske, M.; Someshwar, S. (European Journal of Pediatric Dermatology, 2023)
Trichotillomania (TTM) is a psychodermatological disorder characterized by an uncontrollable urge to pull out hair and may be associated with depression and obsessive-compulsive disorder. Attention deficit hyperactivity disorder (ADHD) is a developmental neuropsychological disorder characterized by pervasive and disabling symptoms of inattention, hyperactivity, and impulsivity. Trichotillomania (TTM) and ADHD often appear to co-occur in children. A poor diet deficient in vitamin D can cause ADHD. A nine-year-old girl came to the observation because, according to her mother, she subconsciously pulled her hair. A thorough history strengthened the clinical suspicion of TTM. The diagnosis of TTM was confirmed by a trichoscopy and an in-depth psychiatric evaluation which highlighted ADHD with prevalent attention deficit. Her vitamin D levels were low (14.1 ng/dL). Adequate psychiatric and dermatological treatment and the intake of vitamin D taken for 1 month on pediatric advice led to evident growth of unusually curly hair after 5 months.